Adult Children’s Timing of Entry into Parenthood - de Bel, Vera; Danielsbacka, Mirkka; Jokela, Markus; Rotkirch, Anna; Tanskanen, Antti O. (Springer Nature, 2026)
Highly educated individuals have their first child at later ages compared to less-educated individuals, and parental investment is associated with the childbearing of adult children. However, no studies have explored the association between maternal and paternal investment and the timing of parenthood for adult daughters and sons, and whether this association varies by education level. Based on the parenthood penalty and life-history theory, it is hypothesized that parental investment decreases the age at first birth of highly educated adult children and increases the age at first birth of less educated and those currently enrolled in education, particularly between mothers and adult daughters. Event-history analyses were conducted on 4,111 participants and 894 first births from 13 waves of the longitudinal and population-based German Family Panel Analysis of Intimate Relationships and Family Dynamics Study (Pairfam). Results show that contact with mothers was associated with earlier parenthood in less-educated adult children and later parenthood in highly educated adult children. However, contact with fathers was associated with later parenthood in currently enrolled adult children and earlier parenthood in highly educated adult sons. Europe's fertility decline is largely due to delayed age at first birth and parental investment in adult children can contribute to and counteract this trend.